(untitled) (Journal of Pharmaceutical Negative Results, 2022)
An economic evaluation of the effect of irrigating tomato plants with agricultural drainage water remediated with DHS technology was conducted in a field experiment at Rahawy, Giza governorate. According to the findings, Egypt's reuse of agricultural drainage water meets around 15% of its irrigation needs, while the overall expenses of remediating one cubic metre of agricultural drainage water using DHS technology reached LE 1.03. The volume of irrigation water used to grow tomato plants decreased by 5% in non-remediated soil ecosystems, 14% in soil ecosystems remediated by microbial inoculation and fortified by bentonite clay mineral, and 22% in soil ecosystems receiving a mix of clay minerals, rock phosphate, and sulphur and inoculated by Thiobacillus sps and phosphate dissolving bacteria PDB. the productivity of one feddan of tomato crop irrigated with non-remediated agricultural drainage water reached 11.31 tons per feddan, irrigation with agricultural drainage water increased tomato crop by about 31%, all studied indicators of the economic efficiency of tomato production grown in remediated soil ecosystem and irrigated with remediated agricultural drainage water were higher than their counterparts grown in non-remediated soil ecosystem and irrigated with non-remediated agricultural drainage water, total tomato yield increased under irrigation with remediated agricultural drainage to LE 31.668, reaching 47% over its counterpart grown in non-remediated soil ecosystem irrigated with non-remediated agricultural drainage water, the net yield per feddan increased by 716% under irrigation with remediated agricultural drainage water over its counterpart irrigated with non-remediated agricultural drainage water. When irrigated with remediated agricultural drainage water, the cost of one tonne of tomato fruits harvested from non-remediated, remediated with bacteria, or remediated with clay minerals soil ecosystems decreased by 11%, 40%, and 44%, respectively, when compared to its counterparts irrigated with non-remediated agricultural drainage water. The profitability of one pound spent on tomato fruits harvested from non-remediated, remediated with bacteria, or remediated with clay minerals soil ecosystems decreased by 598 percent, 1010 percent, and 163 percent more than its counterpart irrigated with non-remediated agricultural drainage water, respectively, under irrigation with remediated agricultural drainage water. The net return of the water unit increased by 761 percent, 1367 percent, and 282 percent in tomato fruits harvested from non-remediated, remediated with certain microorganisms, or remediated with clay minerals soil ecosystems under irrigation with remediated agricultural drainage water, respectively, over its counterpart irrigated with non-remediated agricultural drainage water. The estimated profitability of each pound spent on agricultural drainage water remediation was LE 2.36 for tomato plants growing in an unremediated soil ecosystem, LE 10.07 for those remediated with specific microbes, and LE 33.43 for those remediated with clay minerals. The economic valuation of irrigating tomato plants with agricultural drainage water remediated with DHS technology was good, which will support farmers' social acceptance and sustainability of DHS use.